Using big data to analyze the vaccination status of children with congenital heart disease in Yinzhou District, China - Lin Zhang; Ziliang Yang; Yueqi Yin; Wenzan Huang; Tianfei Yi; Jianming Ping; Liya Liu; Peng Shen; Yexiang Sun; Hongbo Lin (Human Vaccines & Immunotherapeutics)
Congenital heart disease (CHD) represents a significant population warranting particular attention concerning vaccination coverage. To comprehend the vaccination status of CHD within Yinzhou District, Ningbo City, China, and to facilitate the formulation of preventive, control, and immunization strategies against vaccine-preventable diseases in children with congenital heart conditions. Using the China Yinzhou Electronic Health Record Study (CHERRY) database, we analyzed the vaccination coverage of children with CHD born between January 1, 2016 and September 20, 2021, and analyzed the influencing factors associated with the level of vaccination coverage. This study involved 762 children diagnosed with CHD at the age of 12 months, revealing that 86.74% of these children had received at least one dose of the National Immunization Program (NIP) vaccines. The coverage for non-NIP vaccines, such as the rotavirus vaccine, influenza vaccine, Influenza Haemophilus influenzae Type b (Hib) Conjugate Vaccine, 13-valent pneumococcal conjugate vaccine (PCV13), and inactivated enterovirus type 71 vaccine (EV71), stood at 27.30%, 7.74%, 63.25%, 33.76%, and 34.51%, respectively. The completion coverage for the entire vaccination schedule were 27.30%, 5.51%, 55.77%, 34.25%, and 25.59%, respectively. There was a statistically significant correlation between vaccination coverage in classification of diagnostic medical institutions and the types of diagnosed diseases. Compared to their typically developing counterparts, 12-month-old children afflicted with CHD exhibit a slightly diminished vaccination coverage, alongside a discernible inclination toward delayed vaccination. Notably, the determination to undergo vaccinations seems predominantly influenced by the classification of diagnostic medical institutions. In practical terms, proactive measures involving early diagnosis, comprehensive health assessments, and timely interventions ought to be implemented to enhance vaccination rates while prioritizing safety.